Pride & puppies - Shane, Lizzie (Shane, Lizzie. Pine Hollow series., 2023)
"Dr. Charlotte Rodriguez has a history of dating jerks-and she blames Jane Austen. She made the brooding Darcy types sound so appealing, but when Charlotte is dumped by the latest in a long line of not Darcy-caliber boyfriends she decides to swear off men and convinces her best friends to join her in a Puppy Pact, lavishing all their affection on sweet little puppies who actually deserve it instead of the man-children who most definitely do not. The absolute last person she expects to tempt her back into the dating pool is the new physical therapist in town, George Leneghan. George is a total teddy bear-and not at all Charlotte's type-but he's kind, he's patient, and he's determined to get out of the Friend Zone. Now all he has to do is convince Charlotte that the best heroes wear their hearts on their sleeves"--